The Accounting Education and the Accounting Profession: Today and Looking Ahead - Fanya Filipova (Икономика и компютърни науки)
The subject of the report is accounting education and the accounting profession, with the focus on their current state (in Bulgaria and around the world), and the possible directions in their development are outlined. The tasks set by the author are to clarify the state of accounting education and the accounting profession; the interest, supply, demand and realization of accounting specialists, as well as the problems to be solved. The research approach is mainly qualitative, based on the author's teaching experience (37 years) and practice as a CPA (29 years), including an analysis of the literature on the subject. Some quantitative (statistical) data were also used, but only to illustrate some of the author's statements. The limitations of the study are related to the lack of publicly available information in Bulgaria on the number of students studying at Bulgarian universities in the specialty "Accounting", as well as data on the number of specialists employed in the field of accounting. The main conclusions are related to the understanding that the future of the accounting profession is directly dependent on its ability to perform new functions, through which to create benefit and value for enterprises. This requires a change in education and training by including academic disciplines that would integrate accounting knowledge with financial, business knowledge, management skills, and technology. The need for increasingly active communication in education with representatives of practice and with professional organizations of accountants/auditors is emphasized. It is necessary to seek approaches and means for developing the analytical, strategic, and managerial thinking of future accountants, at the expense of the currently prevailing study of regulatory acts and the development only of technical skills related to debiting and crediting accounts. Teamwork skills; communication skills; high foreign language training, including in the field of specialized professional knowledge and terminology, must be improved. It is imperative to improve computer training, especially that related to direct professional duties such as: working with office packages; with specialized accounting software; working with ERP systems; working with large databases (Big Data) based on AI.